HUBUNGAN BEBAN KERJA FISIK DENGAN NYERI MUSCULOSKELETAL DISORDERS PADA PEKERJA PABRIK TAHU JAKARTA TIMUR - Sri Yurnia Pratiwi (2023)
Background: Musculoskeletal problems are produced when muscles are subjected to excessive work loads many times in a long enough time and result in injuries to joints, ligaments and tendons. Workload is also one of the factors that contribute to musculoskeletal problems. Objective: to find out whether the physical demands of tofu factory workers in East Jakarta are related to musculoskeletal problems. Method: The research method used is quantitative observational with a cross sectional approach. As many as 60 tofu factory workers participated in this study, the parameters used were the oximeter to assess physical workload and the Nordic Body Map questionnaire to assess musculoskeletal disorders pain. Results: this study used the Spearman correlation test to obtain a value of p = 0.16 (<0.05) and the value of the correlation coefficient on physical workload was valued at r=0.311 Conclusion This indicates that there is a relationship between physical workload and musculoskeletal disorders pain in East Jakarta Tofu factory workers with a moderate level category.